Abstract Translation in Scientific Writing by Non-English Major Student using Google Translate - Nyayu Yayu Suryani; Tira Nur Fitria (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
The main purpose of this research is to find out Google Translate errors when translating bachelor's paper abstracts from Indonesian to English. Six abstracts of Non-English major undergraduate student papers from diverse faculties Sekolah Tinggi Ilmu Kesehatan Siti Khadijah Palembang were chosen at random. Following that, the data is compared for each sentence segment, as well as any words or phrases with problems are investigated. The result shows that the primary errors of abstract translations include lexicosemantic, tense, preposition, word order, distribution, and use of verb group, as well as active and passive voice errors. Abstract translation outcomes deviate significantly from expectations. Both translating English writings into Indonesian and Indonesian texts into English takes advanced translation abilities. Regarding translation, several factors should be considered; they include the linguistic system utilized for both languages and the cultural understanding of the two languages. In the case of scientific writing translation, involve a translator in improving the quality of translation. In terms of academics, it is recommended that further research be done on comparable challenges in abstract translation, but with more variety from diverse sources.